2005
DOI: 10.2460/javma.2005.227.768
|View full text |Cite
|
Sign up to set email alerts
|

Association between exercise-induced pulmonary hemorrhage and performance in Thoroughbred racehorses

Abstract: Results suggest that EIPH is associated with impaired performance in Thoroughbred racehorses not medicated with furosemide and not using nasal dilator strips.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
121
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(135 citation statements)
references
References 10 publications
(3 reference statements)
9
121
1
4
Order By: Relevance
“…Factors that make this an important issue include the frequency of EIPH, the importance of the disease in terms of the performance and well-being of horses, and the common use of prophylactic treatments. At least 80% of racehorses can be expected to develop the condition at some time during their career, 1,2 approximately 60% of sudden deaths during racing have been attributed to pulmonary hemorrhage, 2 severe EIPH has been shown to adversely affect race performance, 3 and EIPH is believed to adversely affect the overall health of racehorses. 4 Beyond this, Objective-To evaluate the efficacy of furosemide for prevention of exercise-induced pulmonary hemorrhage (EIPH) in Thoroughbred racehorses under typical racing conditions.…”
mentioning
confidence: 99%
“…Factors that make this an important issue include the frequency of EIPH, the importance of the disease in terms of the performance and well-being of horses, and the common use of prophylactic treatments. At least 80% of racehorses can be expected to develop the condition at some time during their career, 1,2 approximately 60% of sudden deaths during racing have been attributed to pulmonary hemorrhage, 2 severe EIPH has been shown to adversely affect race performance, 3 and EIPH is believed to adversely affect the overall health of racehorses. 4 Beyond this, Objective-To evaluate the efficacy of furosemide for prevention of exercise-induced pulmonary hemorrhage (EIPH) in Thoroughbred racehorses under typical racing conditions.…”
mentioning
confidence: 99%
“…Some degree of exercise-induced pulmonary haemorrhage occurs in almost all racehorses actively involved in training or racing (McKane et al 1993). According to Hinchcliff et al (2005), the low grade of EIPH is not associated with reduced athletic per-doi: 10.17221/8878-VETMED formance. We can suppose that the finding of 11% of hemosiderophages in BAL fluid is suggestive of previous mild pulmonary haemorrhage and is probably not associated with reduced athletic performance in this horse.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies by Geor et al (2001) in race horses showed that the simultaneous use of nasal patches and furosemide attenuated the presentation of EIPH and diminished the presence of erythrocytes in the BALF. In addition, Hinchcliff et al (2005) suggested that EIPH is associated with impaired performance in thoroughbred racehorses that are not medicated with furosemide and do not use nasal dilator strips.…”
Section: Treatment Of Exercise-induced Pulmonary Haemorrhagementioning
confidence: 99%
“…These authors mentioned the demand that exists for prevention and treatment methods to control bleeding. Therefore, a series of manipulations and drug treatments have been researched and tested, but just few of them have demonstrated efficacy (Hinchcliff 2005). However, furosemide is the drug of choice in treating this condition (Hinchcliff et al 2009).…”
Section: Treatment Of Exercise-induced Pulmonary Haemorrhagementioning
confidence: 99%